PENGARUH STRUKTUR KEPEMILIKAN TERHADAP RETURN SAHAM - Etty Murwaningsari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
The objective of this research is to analyze whether the factors such as institutionalownership and managerial ownership have influence to stock return. Sample inthis research consists of 53 manufacture and service industries that have listed inIndonesian Stock Exchange between the year 2001-2007 taken using purposivesampling method. Data analysis uses classical assumption tests prior to Multipleregressing Testing. The result of this research showed that on a significant rate5%, institutional ownership and managerial ownership have a positive andsignificant influence on stock return. While control variable gain or loss oncurrency, size and earnings volatility also proved to have significant influence onstock return. Only negative earnings hypothesis cannot be proven.Keyword: stock return, institutional ownership, managerial ownership, negativeearnings, gain or loss on currency, size and earnings volatility.